Hubungan antara konsumsi makanan goitrogenik dan status iodium pada ibu hamil di kecamatan endemis gangguan akibat kekurangan iodium - Eko Budi Santoso; Hamam Hadi; Toto Sudargo (Fakultas Kedokteran Universitas Gadjah Mada, 2006)
Background: Iodine Deficiency Disorder (IDD) is a nutrition problem in Indonesia, particularly endemic in Gunungkidul District. Contribution of goitrogenic food to IDD is not known yet in the population.Objectives: To identify the relationship between consumption pattern of pregnant mothers, especially intake of iodine, goitrogenic, and protein, and urine iodine level.Methods: This was an observational study which used a cross sectional design with both quantitative and qualitative approaches. Subjects of the study were pregnant mothers with gestational period between 13 to 24 weeks. Data consisted of characteristics of pregnant mothers, consumption pattern, and urine iodine level. Survey of consumption used food frequency questionnaire method. Data were descriptively and analytically processed using chi square and multiple regression test.Results: There was a relationship between iodine intake and urine iodine excretion. Pregnant mothers with low iodine intake had a risk 6,7 times higher to low iodine excretion